THE GLOBAL COMPETITION IN THE DIGITAL SOCIETY 5.0 ERA: THE CHALLENGES OF THE YOUNGER GENERATION - Apdillah, Dicky; Panjaitan, Khairunnisak; Stefanny, Nandika Tiara Puteri; Surbakti, Febby Andriana (Transpublika Publisher, 2022)
The millennial generation has rapidly taken over the workforce, posing new challenges to global competition in the era of Digital Society 5.0. According to surveys, millennials are technologically savvy. The ability of businesses to consistently enhance performance is contingent on their ability to retain and develop the millennial generation. The development of high-quality human resources (HR) among the millennial generation is a challenge in the era of digital society's global competition. 5.0. The millennial generation is inextricably linked to the Industrial Revolution 4.0, often known as the Fourth Industrial Revolution. Hence, it can be stated that human resource development is critical in current era, where the revolution is centered on the pattern of digitalization and automation in all spheres of human life. A good and excellent education system, particularly in terms of educational quality and relevance to community and work demands, is a major priority for creating human resources for the millennial generation.